Subdiffraction‐limited chemical imaging of patterned phthalocyanine films using tip‐enhanced near‐field optical microscopy. (1st July 2016) - Hermann, R.; Gordon, M. J.
Abstract : A tip‐enhanced near‐field optical microscope, based on a shear‐force atomic force microscope with plasmonic tip coupled to an inverted, confocal optical microscope, has been constructed for nanoscale chemical (Raman) imaging of surfaces. The design and validation of the instrument, along with its application to near‐field Raman mapping of patterned organic thin films (coumarin‐6 and Cu(II) phthalocyanine), are described. Lateral resolution of the instrument is estimated at 50 nm (better than λ/10), which is roughly dictated by the size of the plasmonic tip apex. Additional observations, such as the distance scaling of Raman enhancement and the inelastic scattering background generated by the plasmonic tip, are presented. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A tip‐enhanced near‐field optical microscope has been developed and used to chemically image patterned Cu (II) phthalocyanine thin films with spatial resolution better than 50 nm (<λ/10). Near‐field spectra of coumarin‐6 films and the distance scaling of Raman enhancements are also presented.